Principles and Strategies for Determining Quality Standards for Graduate Competencies in Improving Soft Skills in Islamic Universities - Subagiya, Bahrum (Journal of Multidisciplinary Science, 2024)
Improving the quality of education in higher education is an urgent need for immediate improvement, especially in the soft skills of graduates. The purpose of this research is to find out an overview of what Ibn Khaldun University of Bogor does in designing principles and strategies for determining the quality standards of graduate competencies in soft skills. This research uses a qualitative approach with a case study with data analysis techniques following the concept of Milles and Hubbermen. The results showed that in building graduates' soft skills, Ibn Khaldun University of Bogor based it on a religious foundation, by teaching Islamic studies that must be taken by students for four semesters. Students are equipped with teaching and understanding of aqidah, sharia, morals, and Islamic Worldview. In addition, students are also strengthened spiritually by participating in a mandatory activity, "Bina Baca Al-Qur'an Intensif" to improve their relationship with the Al-Qur'an and also improve the quality of their worship. All activities are monitored directly under the supervision of the Vice-Chancellor for Academic Affairs.